Analysis of process parameters influence on syngas yields and biomass gasification rates in a continuous particle-fed solar-irradiated gasifier - Srirat Chuayboon; Stphane Abanades; Sylvain Rodat (My University, 2020)
Steam gasification of biomass was experimentally investigated with different lignocellulosic biomass feedstocks in a 1.5 kWth continuous particle-fed solar-irradiated gasifier at high temperatures (1100-1300 °C) utilizing highly concentrated sunlight as process heat source, demonstrating the conversion of intermittent solar energy and biomass into synthesis gas without CO2 emissions. Forty-nine on-sun experiments were performed in order to study the effect of process parameters (biomass feeding rate, temperature, biomass composition) on syngas production yield, biomass gasification rate (carbon conversion rate), and reactor performance. As a result, syngas yield, composition (quality), biomass gasification rate, and reactor performance increase significantly with both the biomass feeding rate and temperature because both biomass consumption rates and reaction kinetics are enhanced. However, the performance outputs are reduced when biomass feeding rate exceeds its optimal feeding point. The reactor temperature of 1300°C is recommended to operate reliably the solar biomass gasifier with the considered biomass particle size range (0.3-4 mm) in a continuous feeding mode with complete biomass conversion, as verified by the carbon consumption rate that matches closely the carbon feeding rate. By optimizing biomass feeding rate consistently with operating temperature, the calorific value of the biomass feedstock is solar upgraded by 24% with carbon conversion extent above 90% and solar-to-fuel energy conversion efficiency up to 29%.
Keywords: Wood gas generator; Carbon fibers; Biomass to liquid; Heat of combustion; Chemical Looping and Thermochemical Processes